DIGITALIZATION LEARNING FOR PASSIVE SPEAKERS: A PHENOMENOLOGICAL APPROACH AT PKPBA UIN MAULANA MALIK IBRAHIM MALANG - Tarmizi, Ahmad; Fikri, Shofil; Qomariah, Rafi'atun Najah; Lazregue, Shofia (UIN Maulana Malik Ibrahim Malang, 2025)
Digitalization in the 5.0 era indirectly requires educators to become promoters in the development of learning in an institution. The ease or the convenience of digitalization supported by smartphones really supports effective, innovative and fun learning. Therefore, in Independent Learning, it’s necessary to make efforts to develop Arabic language learning, i.e. fun, easy and habitual, as is carried out by the Intensive of Arabic Language Program at UIN Maulana Malik Ibrahim Malang. This qualitative research used a phenomological approach with the steps: Bracketing, Intuiting, Analyzing, and Describing. The results of this research; 1) Learning in the Digital Era can be done by designing textbooks that are equipped with applicable barcodes and application links. 2) Learning using smartphones becomes effective, innovative and fun. 3) Learning with digital devices can be done anywhere, not necessarily in the classroom. The novelty of this research is learning Arabic for non-Arab speakers by digitalizing learning to support the Indonesian government's independent learning program